SketchScape: transforming 2D landscape sketches into immersive 3D paper art - Mat Nayan, Nadiyanti; Bahaluddin, Azrul; Hamzah, Helmi (2025)
In landscape architecture education, 2D sketches serve as vital tools for conceptualizing spatial ideas. However, they often fall short in communicating depth, elevation, and the immersive qualities of landscape design. SketchScape is a creative pedagogical initiative that transforms traditional 2D landscape sketches into tangible 3D paper sculptures, bridging the gap between static representations and spatial comprehension. This project draws exclusively from A Student’s Guide to Landscape Architecture, a textbook authored and illustrated by lecturers within the same academic programme. By converting these familiar teaching materials into layered, cut-paper models, SketchScape reinforces a shared visual language while introducing an innovative medium that enhances both engagement and understanding. The transformation process involves four stages: sketch selection, digital vectorization, 3D modelling, and paper engineering. Vectorized sketches are modelled in CAD software to simulate terrain and elevation, then fabricated using paper cutting and manual assembly techniques. Tested among 98 students in the Landscape Architecture Programme, the models allowed learners to interact with spatial forms in a hands-on and creative way. Results show that this method significantly improves spatial awareness and design literacy. Students reported stronger engagement, better understanding of topographic relationships, and increased motivation to explore design variations. SketchScape successfully integrates traditional drawing methods with modern fabrication techniques, offering a compelling educational tool that makes landscape architecture more accessible, interactive, and creatively rich. This approach reaffirms the importance of multisensory, interdisciplinary learning and underscores the potential of merging artistic processes with architectural education.